Pemanfaatan Seft Sebagai Modalitas Therapy Community (TC) Untuk Kesehatan Mental Dan Spiritual Pecandu Napza - Inggriane Puspita Dewi; Siti Ulfah Rifa’atul Fitri (LPPM UMRI, 2020)
National Narcotics Agency (BNN) of Bandung records that there are 25,000 young people in Bandung who are drug users. Based on the results of interviews with ten prisoners said they often feel bored, stressed, depressed, sad and hopeless. Based on this phenomenon it was necessary to support rehabilitation programs for drug addicts through therapy with a spiritual approach. A spiritual approach is Spiritual Emotional Freedom Technique (SEFT) therapy, which is a combination of Spiritual Power and Energy. The results of the activity showed that the participants were able to do self-healing using the SEFT method, which was felt to be effective in helping participants manage emotional and spiritual problems during the prison, evidenced by an increase in the percentage of self-control ability and a positive effect, while anxiety and depression decrease. Participants also experienced an increase in the percentage of positive religious coping. Therefore, prisons are advised to keep monitoring self-healing activities with SEFT which is recommended to be routinely carried out by rehabilitation participants even though the program has finished, because at any time the participants' mental and spiritual health conditions may change. Keywords : addicted, SEFT, spiritual, mental